Brand Image and Value on the Purchasing Decision of Coffee Drinks At the Outlet of Janji Jiwa Royal Plaza Surabaya: Brand Image (International Journal of Scientific Research and Management (IJSRM), 2020)
In order to maintain the existence of the business, it always creates and implements various marketing strategies to maintain and maintain business operations in the midst of fierce business competition. All businesses have competition so this makes the company must have a strategy to be able to excel in competition. Companies must be able to know how to retain their customers so as not to turn to competitors. Especially in the field of coffee drinks business which is currently being rife in Surabaya. This research uses a Quantitative Approach is a research approach that uses data in the form of figures from survey answers distributed to research samples and analyzed using statistical analysis techniques. The partial regression results (t-test) showed the results of the brand image proved to have a significant effect on the decision to purchase coffee drinks at Janji Jiwa Royal Plaza Surabaya. Value is proven to have a significant effect on coffee beverage purchase decisions at Janji Jiwa Royal Surabaya. Simultaneous regression analysis (F-test) proved to have a significant effect on brand image and value on coffee beverage purchase decisions at Janji Jiwa Royal Surabaya.